Data Scientists’ Skills in Detecting Archetypes in Iran - Hamideh Iraj; Babak Sohrabi (JOIV : International Journal on Informatics Visualization, 2017)
The use of data-driven decision making and data scientists is on the rise in Iran as companies have rapidly been focusing on gathering data and analyzing it to guide corporate decisions. In order to facilitate the process and understand the nature and characteristics of this transformation, the current study intends to learn about data scientists’ skills and archetypes in Iran. Detecting skills archetypes has been done via analyzing the skills of data scientists which were self-expressed through an online survey. The results revealed that there are three archetypes of data scientists including high level data scientists, low level data scientists and software developers. The archetypal patterns are based on levels of data scientists’ skills rather than the type of dominant skills they possess which was the most frequent pattern in previous studies.